Unravelling the role of Sildenafil and SB204741 in suppressing fibrotic potential of peritoneal fibroblasts obtained from PD patients - Chaturvedi, Saurabh; Singh, Harshit; Agarwal, Vikas; Jaiswal, Akhilesh; Prasad, Narayan (Frontiers in Pharmacology, 2024)
Introduction: Peritoneal fibrosis (PF) results in technique failure in peritoneal dialysis (PD) patients. Peritoneal fibroblasts are characterized by increase in the ACTA2 gene, responsible for alpha smooth muscle actin (α−SΜΑ), extracellular matrix (ECM) production, and inflammatory cytokines production, which are the are key mediators in the pathogenesis of PF. 5-hydroxytryptamine (5-HT; serotonin) induces ECM synthesis in fibroblasts in a transforming growth factor-beta 1 (TGF-β1) dependent manner. The purpose of our study was to identify the potential mechanism and role of sildenafil and 5HT2B receptor inhibitor (SB204741) combination in attenuating PD-associated peritoneal fibrosis. Methods: Studies were performed to determine the effect of TGF-β1, sildenafil, and SB204741 on human peritoneal fibroblasts (HPFBs) isolated from the parietal peritoneum of patients in long-term PD patients (n = 6) and controls (n = 6). HPFBs were incubated with TGF-β1 (10 ng/mL) for 1 h and later with TGF-β1 (10 ng/mL)/[sildenafil (10 µM) or SB204741 (1 µM)] and their combination for 24 h (post-treatment strategy). In the pre-treatment strategy, HPFBs were pre-treated with sildenafil (10 µM) or SB204741 (1 µM) and a combination of the two for 1 h and later with only TGF-β1 (10 ng/mL) for 24 h. Results: The anti-fibrotic effects of the combination of sildenafil and SB204741 were greater than that of each drug alone. In TGF-β1-stimulated HPFBs, pro-fibrotic genes (COL1A1, COL1A2, ACTA2, CTGF, FN1, and TGFB1) exhibited higher expression than in controls, which are crucial targets of sildenafil and SB204741 against peritoneal fibrosis. The synergistic approach played an anti-fibrotic role by regulating the pro- and anti-fibrotic gene responses as well as inflammatory cytokine responses. The combination treatment significantly attenuated peritoneal fibrosis, as evident by the almost complete amelioration of ACTA2 expression, restoration of anti-fibrotic genes (MMP2/TIMP1), and, at least, by reducing the expression of pro-inflammatory cytokines (IFN-γ, IL-4, IL-17, IL-1β, IL-6, TNF-α, and TGF-β1) along with an increase in IL-10 levels. Discussion: Taken together, the above research evidences that the combination of sildenafil and SB204741 may have therapeutic potential in suppressing peritoneal fibrosis due to peritoneal dialysis.